Cost Aspect in the Stability Analysis of an Earthfill Dam with Respect to Variations in Embankment Materials and Water Levels (Case Study: Cibeet Dam Project, Bogor Regency) - Muhammad Faizal; Muhammad Zaki (Green Publisher Indonesia, 2026)
Stability analysis was carried out using PLAXIS 2D based on the Finite Element Method with the Shear Strength Reduction (SSR) approach. Two design alternatives were evaluated: Model 1 with a complete material zoning system consisting of sand–gravel, sandstone, and coarse filter layers, and Model 2 with a simplified configuration dominated by sandstone material. The evaluation was performed under Low Water Level (LWL), Normal Water Level (NWL), and Flood Water Level (FWL) conditions, as well as under static loading, Operating Basis Earthquake (OBE), and a design earthquake with a magnitude of 7.5. The results indicate that increasing reservoir water levels and seismic loading lead to a reduction in the Safety Factor (SF); however, all analyzed conditions still satisfy the required stability criteria. Model 2 exhibits higher SF values under static conditions, while Model 1 demonstrates superior stability performance under strong earthquake loading and long-duration seismic events. Cost analysis shows that the total construction cost of Model 1 is IDR 566.85 billion, whereas Model 2 requires IDR 558.86 billion, resulting in a cost saving of 1.41% for Model 2. The integrated analysis reveals a clear trade-off between stability and cost, where Model 1 provides higher technical safety, while Model 2 offers greater economic efficiency.